IMPLEMENTASI PENAFSIRAN SURAT AN NISA’ 101 BAGI SUPIR BUS ANTAR PROVINSI - Syaikhul Hakim (LPPM Institut Agama Islam Al-Hikmah Tuban, 2015)
The sura an Nisa' 101 is a verse that describes the permissibility of qasar prayers, although the there are still debates among the Muslim scholars in understanding the verse in terms of the qasar prayers, be they allowed under fear conditions (khauf) or in a safe condition. The criteria for traveling for being allowed to perform qasar prayers is not described in the sura an Nisa' (4:101), but an explanation of the criteria for traveling for being allowed to perform qasar prayers is described in the hadith of the Prophet (PBUH). In terms of the mileage of traveling that allows to perform qasar prayers, there are differences of viewpoints among Islamic jurists. All is because of the results of so-called isntimbat al-hukm from different hadith, resulting in different understandings. According to Abu Hanifah the mileage allowed to perform qasar prayers is 81 KM; while according to such Islamic jurists as Syafi'i, Maliki, Hanbali, the mileage allowed to perform qasar prayers is 89 KM. Those who become inter-provincial bus drivers are considerably eligible to perform qasar prayers, because they have met the criteria established by mufassir (Qur'anic interpretators)